Childcare as a social determinant of access to healthcare: a scoping review - Megan McArthur; Persephone Tian; Kimberly A. Kho; Kavita P. Bhavan; Kavita P. Bhavan; Bijal A. Balasubramanian; Bijal A. Balasubramanian; Anisha P. Ganguly (Frontiers in Public Health)
IntroductionAs health systems strive to screen for and address social determinants of health (SDOH), the role of access to childcare and barriers to healthcare posed by childcare needs remains underexplored. A gap exists in synthesizing existing evidence on the role of access to childcare as a SDOH.MethodsThis scoping review aimed to examine and analyze existing literature on the role of childcare needs as a social determinant of access to healthcare. We conducted a structured literature search across PubMed, Scopus, health policy fora, and professional healthcare societies to inclusively aggregate studies across interdisciplinary sources published between January 2000 and June 2023. Two independent reviewers reviewed results to determine inclusions and exclusions. Studies were coded into salient themes utilizing an iterative inductive approach.ResultsAmong 535 search results, 526 met criteria for eligibility screening. Among 526 eligible studies, 91 studies met inclusion criteria for analysis. Five key themes were identified through data analysis: (1) barriers posed by childcare needs to healthcare appointments, (2) the opportunity for alternative care delivery models to overcome childcare barriers, (3) the effect of childcare needs on participation in medical research, (4) the impact of the COVID-19 pandemic on childcare needs, and (5) the disproportionate burden of childcare experienced by vulnerable populations.DiscussionChildcare needs remain underexplored in existing research. Current evidence demonstrates the relevance of childcare needs as a barrier to healthcare access, however dedicated studies are lacking. Future research is needed to understand mechanisms of childcare barriers in access to healthcare and explore potential interventions.